SERUM SELENIUM AND GLUTATHIONE-PEROXIDASE ACTIVITIES AND THEIR INTERACTION WITH TOXIC METALS IN DIALYSIS AND RENAL-TRANSPLANTATION PATIENTS - TURAN, B; DELILBASI, E; DALAY, N; SERT, S; AFRASYAP, L; SAYAL, A (HUMANA PRESS INC, 1992)
Selenium, aluminum, cadmium, and magnesium concentrations and gluthathione-peroxidase activities in sera of 35 healthy individuals, 30 renal transplants, and 30 hemodialysis patients were measured. Serum selenium, aluminum, and cadmium concentrations in both groups of patients were higher than the controls (p < 0.001), whereas the serum gluthathione-peroxidase levels were lower (p < 0.001). According to our results, it can be concluded that the patients receiving hemodialysis are subjected to more toxic elements than the transplantation patients. These findings imply that dietary selenium supplement may be suggested in renal failure for the detoxification of elements, such as cadmium and mercury. The essential trace element selenium takes part not only in the direct protection of endothelial cells against the accumulation of aggressive oxygen species, but also in the prevention of the toxic effects of cadmium or in the modulation of the active calcium transport.
Keywords: SELENIUM; GLUTATHIONE PEROXIDASE; TOXIC METALS; SERUM; HEMODIALYSIS; RENAL TRANSPLANTATION; BLOOD-CELL ZN; GLUTATHIONE-PEROXIDASE; LIPID-PEROXIDATION; DIETARY SELENIUM; CADMIUM; MERCURY; PLASMA; OSTEODYSTROPHY; METABOLISM; ALUMINUM; Biochemistry & Molecular Biology; Endocrinology & Metabolism